The effect of noise pollution on animal welfare - a case study in balb/c mice - Ramos, Jaciara Andrade; Vicentine, Karina Ferrazzoli Devienne; Pelli, Afonso (Seven Editora, 2023)
The quality of life is determined primarily by the quality of the environment. Many variables act on the environment, including noise pollution, present in everyday life. According to the World Health Organization, above 55 db, the body begins to suffer the impact of noise, causing mild stress and excitement. One of the main responses is activation of the hypothalamic-pituitary-adrenal axis, causing the release of glucocorticoids. These hormones act on the energy metabolism, increasing the amount of free fatty acids in the bloodstream. Thus, changes in lipid metabolism have been reported after stressful situations. In this experiment we used Mus musculus balb/c mice submitted to chronic sound stress, at 90dB, for 30 days, at night, from 8 pm to 2 am the next day. The animals were euthanized by decapitation after anesthesia, and the blood collected was used to measure cholesterol, triglycerides, and glucose. During the experiment the animals’ weight was monitored, and there was no considerable variation between the control and experimental groups. Regarding the biochemical parameters, there were statistically significant differences in the levels of cholesterol, triglycerides, and glucose. The significance levels, or p values, were 0.067 (p less than 6.7%); 0.053 (p less than 5.3%), and 0.000 (p less than 0.0009%), respectively. With the present study, it can be concluded that stress hormones interfere with cholesterol, triglyceride and glucose metabolism. The chronic noise stress model can be considered a good environmental stress model that mimics urban stress. DOI: https://doi.org/10.56238/colleinternhealthscienv1-083